# Given that f ( x ) = x 2 − 9 x and g ( x ) = x + 6 , find: a)(f+g)(1) b)(f−g)(1) c)(fg)(1) d)(fg)(1) Given that f ( x ) = ( x − 2 ) 2 and g ( x ) = 5 − 2 x , find: a)(f+g)(−4)= b)(f−g)(−4)= c)(fg)(−4) 1

Given that f ( x ) = x 2 − 9 x and g ( x ) = x + 6 , find:

a)(f+g)(1)

b)(f−g)(1)

c)(fg)(1)

d)(fg)(1)

Given that f ( x ) = ( x − 2 ) 2 and g ( x ) = 5 − 2 x , find:

a)(f+g)(−4)=

b)(f−g)(−4)=

c)(fg)(−4)=

d)(fg)(−4)=

In a Northwest Washington County, the speeding fines are determined by the formula: F ( s ) = 13 ( s − 45 ) + 60 where F ( s ) is the cost in dollars of the fine if a person is caught driving at a speed of s miles per hour. If a fine comes to a total of $ 476 , how fast in mph was the person driving? m p h

Show more * *

*https://orderyourpaper.com/wp-content/uploads/2022/02/Hnet.com-image-10-300x138.png 0 0 oypadmin https://orderyourpaper.com/wp-content/uploads/2022/02/Hnet.com-image-10-300x138.png oypadmin2022-09-20 06:31:432022-09-20 06:31:43Given that f ( x ) = x 2 − 9 x and g ( x ) = x + 6 , find: a)(f+g)(1) b)(f−g)(1) c)(fg)(1) d)(fg)(1) Given that f ( x ) = ( x − 2 ) 2 and g ( x ) = 5 − 2 x , find: a)(f+g)(−4)= b)(f−g)(−4)= c)(fg)(−4) 1*